Ciência, Tecnologia E Inovação: Desafi O Para Um Mundo Global 2 2019
DOI: 10.22533/at.ed.61719230816
|View full text |Cite
|
Sign up to set email alerts
|

Semáforo Inteligente

Abstract: Revisão: Os Autores O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…After analyzing the magazines Veja and Isto É, and the newspapers O Estado de S.Paulo, Folha de S.Paulo, O Globo, and Jornal do Brasil, between 1972and 1992, Barros (2003 found that "the press only began to attribute more importance to the subject when it came to be recognized as scientific knowledge, legitimized by the scientific community and society itself" (p. 85). For this author, the Brazilian press and its discourse on the environment during the aforementioned period was more directly related to official state discourse than it was to scientific discourse.…”
Section: Origins: the Process Of Environmentalizing A Societymentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the magazines Veja and Isto É, and the newspapers O Estado de S.Paulo, Folha de S.Paulo, O Globo, and Jornal do Brasil, between 1972and 1992, Barros (2003 found that "the press only began to attribute more importance to the subject when it came to be recognized as scientific knowledge, legitimized by the scientific community and society itself" (p. 85). For this author, the Brazilian press and its discourse on the environment during the aforementioned period was more directly related to official state discourse than it was to scientific discourse.…”
Section: Origins: the Process Of Environmentalizing A Societymentioning
confidence: 99%
“…In addition to starting to listen to more scientific sources in the 1980s (Barros, 2003) and having journalism be recognized as something important (L. John, personal communication, September and moving it closer to the interests behind ecological movements" (Petrarca, 2008, pp. 38-39).…”
Section: Rio-92mentioning
confidence: 99%